2021
DOI: 10.3390/pharmaceutics13050760
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Potential Theranostic Platforms for Skin Diseases and Aging

Abstract: Extracellular vesicles (EVs), naturally secreted by cells, act as mediators for communication between cells. They are transported to the recipient cells along with cargoes such as nucleic acids, proteins, and lipids that reflect the changes occurring within the parent cells. Thus, EVs have been recognized as potential theranostic agents for diagnosis, treatment, and prognosis. In particular, the evidence accumulated to date suggests an important role of EVs in the initiation and progression of skin aging and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Moreover, ADSC-EVs manifested a superior impact on wound healing than EVs derived from other stem cells, which might be due to their robust angiogenic effect ( 13 ). ADSC-EVs might accelerate skin wound repair by participating in inflammation, angiogenesis, cell proliferation, and extracellular matrix (ECM) remodeling ( 14 , 15 ), regulating cell apoptosis and autophagy ( 16 , 17 ), and relieving oxidative stress in the wound microenvironment ( 18 ). The regeneration of skin appendages and recovery of physiological functions are also promoted by ADSC-EVs ( 19 , 20 ), which is essential for ideal skin regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ADSC-EVs manifested a superior impact on wound healing than EVs derived from other stem cells, which might be due to their robust angiogenic effect ( 13 ). ADSC-EVs might accelerate skin wound repair by participating in inflammation, angiogenesis, cell proliferation, and extracellular matrix (ECM) remodeling ( 14 , 15 ), regulating cell apoptosis and autophagy ( 16 , 17 ), and relieving oxidative stress in the wound microenvironment ( 18 ). The regeneration of skin appendages and recovery of physiological functions are also promoted by ADSC-EVs ( 19 , 20 ), which is essential for ideal skin regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…EVs have emerged as informative biomarkers with the potential to become a valuable tool for the diagnosis and treatment monitoring of various diseases. EVs can be used as biological indicators for cardiometabolic diseases [ 66 , 67 , 68 , 69 ], neurological diseases [ 70 , 71 , 72 , 73 ], liver diseases [ 74 , 75 ], kidney diseases [ 76 ], respiratory diseases [ 77 ], skin diseases [ 2 , 78 ], and detection of graft rejection [ 79 ]. Small EVs from oral biofluids (i.e., saliva and gingival crevicular fluid) may act as biomarkers for diagnosing oral diseases noninvasively [ 80 , 81 ].…”
Section: Therapeutic Value Of Extracellular Vesiclesmentioning
confidence: 99%
“…For example, human keratinocyte-derived microvesicle miR-21 can promote skin wound healing in diabetic rats by facilitating fibroblast function and angiogenesis (Li et al 2019b), whereas endothelial cell EV-delivered miR-106b delays wound healing through suppression of collagen I content and angiogenesis (Qi et al 2021). Moreover, EV-delivered miRNAs serve as crucial players in mesenchymal stromal cell (MSC) wound therapy (Kim et al 2021). To this end, synovial MSC EV-delivered miR-126-3p (Tao et al 2017), umbilical cord MSC EV-transferred miR-27b (Cheng et al 2020), adipose-derived stem cell-secreted EV enriched with miR-486-5p (Lu et al 2020), and exosomal miR-135a derived from amnion MSCs (Gao et al 2020) have all been shown to accelerate wound healing in murine models.…”
Section: Extracellular Vesicle Mirnas In Wound Healingmentioning
confidence: 99%